Seasonal variations in uterine involution in buffalo following normal puerperium - Abayawansa, W D; Prabhakar, S; Singh, A K; Brar, P S (The Indian Journal of Animal Sciences, 2012)
The present study was conducted on healthy, lactating pleuriparous Murrah buffaloes (29), in their third to fifth parity and calved during December 2007 to May 2008. The animals were selected at 2 organized dairy farms (Mattewara and Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana). On the basis of season of calving they were divided into 2 groups, viz. winter calving buffaloes and summer calving buffaloes. A rapid reduction of uterine body was observed during first 21 days postpartum in both winter and summer calving buffalo. After day 21 postpartum, reduction in uterine body diameter was significantly slower in winter calving buffalo. The diameters of uterine horns rapidly declined during first 14 days postpartum and slowly declined from day 21 to day 35 postpartum in both groups of buffaloes. Ultrasonographic images of contents of postpartum uterine lumen were highly variable within and between animals during the study period. Based on echotexture of the content of uterine lumen 6 grades were identified. Even though uterine tracts reached the pelvic cavity early, the majority of animals in both the groups still had hyperechoic materials with varying amounts at day 63 postpartum indicating incomplete uterine involution. It can thus be concluded that although, season of calving had no significant effect on the initial involution of uterus, reduction in uterine body diameter was significantly affected after day 21 postpartum in both the groups and needs further evaluation with respect to conception.